Molecular modeling and phylogenetic analyses highlight the role of amino acid 347 of the N1 subtype neuraminidase in influenza virus host range and interspecies adaptation - Elli, Stefano; Raffaini, Giuseppina; Guerrini, Marco; Kosakovsky Pond, Sergei; Matrosovich, Mikhail (Frontiers in Microbiology, 2023)
The N1 neuraminidases (NAs) of avian and pandemic human influenza viruses contain tyrosine and asparagine, respectively, at position 347 on the rim of the catalytic site; the biological significance of this difference is not clear. Here, we used molecular dynamics simulation to model the effects of amino acid 347 on N1 NA interactions with sialyllacto-N-tetraoses 6'SLN-LC and 3'SLN-LC, which represent NA substrates in humans and birds, respectively. Our analysis predicted that Y347 plays an important role in the NA preference for the avian-type substrates. The Y347N substitution facilitates hydrolysis of human-type substrates by resolving steric conflicts of the Neu5Ac2-6Gal moiety with the bulky side chain of Y347, decreasing the free energy of substrate binding, and increasing the solvation of the Neu5Ac2-6Gal bond. Y347 was conserved in all N1 NA sequences of avian influenza viruses in the GISAID EpiFlu database with two exceptions. First, the Y347F substitution was present in the NA of a specific H6N1 poultry virus lineage and was associated with the substitutions G228S and/or E190V/L in the receptor-binding site (RBS) of the hemagglutinin (HA). Second, the highly pathogenic avian H5N1 viruses of the Gs/Gd lineage contained sporadic variants with the NA substitutions Y347H/D, which were frequently associated with substitutions in the HA RBS. The Y347N substitution occurred following the introductions of avian precursors into humans and pigs with N/D347 conserved during virus circulation in these hosts. Comparative evolutionary analysis of site 347 revealed episodic positive selection across the entire tree and negative selection within most host-specific groups of viruses, suggesting that substitutions at NA position 347 occurred during host switches and remained under pervasive purifying selection thereafter. Our results elucidate the role of amino acid 347 in NA recognition of sialoglycan substrates and emphasize the significance of substitutions at position 347 as a marker of host range and adaptive evolution of influenza viruses.